2019
DOI: 10.1136/archdischild-2019-esdppp.39
|View full text |Cite
|
Sign up to set email alerts
|

O39 Defining serum CCL22 and trefoil factor 3 (TFF3) as pharmacodynamic biomarkers for use in a proof-of-concept clinical trial of vamorolone in paediatric ulcerative colitis

Abstract: BackgroundPaediatric ulcerative colitis (UC) patients would be well-served by a non-steroidal drug to control mucosal inflammation, without long-term and costly commitment to biologics. Vamorolone is a first-in-class alternative to glucocorticoids (GCs), under development for children with Duchenne muscular dystrophy (DMD); preliminary findings demonstrate improved safety compared with GCs1,2. We sought to define NFkB-regulated, GC-responsive serum biomarkers for use in a proof-of-concept pilot trial of vamoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the same line, Vestergaard [18] performed a study on 19 patients and reported that TFF3 was significantly higher in active individuals than those in clinical remission. Also, Conklin [19] reported that TFF3 levels exhibited a significant correlations with PUCAI index. Moreover, a study on 64 IBD patients assessed by UCEIS and Lichtiger Clinical Activity Index showed that TFF3 was remarkably higher in active patients than quiescent patients [20] .…”
Section: Discussionmentioning
confidence: 98%
“…In the same line, Vestergaard [18] performed a study on 19 patients and reported that TFF3 was significantly higher in active individuals than those in clinical remission. Also, Conklin [19] reported that TFF3 levels exhibited a significant correlations with PUCAI index. Moreover, a study on 64 IBD patients assessed by UCEIS and Lichtiger Clinical Activity Index showed that TFF3 was remarkably higher in active patients than quiescent patients [20] .…”
Section: Discussionmentioning
confidence: 98%